2003
DOI: 10.1086/374943
|View full text |Cite
|
Sign up to set email alerts
|

The Carina Project. I. Bright Variable Stars

Abstract: We present new BV time series data of the Carina dwarf spheroidal galaxy (dSph). Current data cover an area of %0.3 deg 2 around the center of the galaxy and allow us to identify 92 variables. Among them 75 are RR Lyrae stars, 15 are bona fide anomalous Cepheids, one might be a Galactic field RR Lyrae star, and one is located along the Carina red giant branch. Expanding upon the seminal photographic investigation by Saha, Monet, & Seitzer we supply, for the first time, accurate estimates of their pulsation par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…The distance to Carina has been determined using several optical and near-infrared distance indicators, including RR Lyrae stars, the tip of the red giant branch (RGB) and the horizontal branch (HB) level, resulting in a distance of 106 ± 2 kpc or (m − M) V = 20.13 ± 0.04 (Dall'Ora et al 2003;Smecker-Hane et al 1994;Pietrzyński et al 2009). Furthermore, Carina has a core radius of 0.15 degrees (277 pc) and tidal radius of 0.48 degrees (888 pc), as determined from A&A 572, A10 (2014) King-profile stellar density fitting and an estimated extinction of E(B−V) = 0.061, as measured from dust extinction maps (Irwin & Hatzidimitriou 1995;Schlegel et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The distance to Carina has been determined using several optical and near-infrared distance indicators, including RR Lyrae stars, the tip of the red giant branch (RGB) and the horizontal branch (HB) level, resulting in a distance of 106 ± 2 kpc or (m − M) V = 20.13 ± 0.04 (Dall'Ora et al 2003;Smecker-Hane et al 1994;Pietrzyński et al 2009). Furthermore, Carina has a core radius of 0.15 degrees (277 pc) and tidal radius of 0.48 degrees (888 pc), as determined from A&A 572, A10 (2014) King-profile stellar density fitting and an estimated extinction of E(B−V) = 0.061, as measured from dust extinction maps (Irwin & Hatzidimitriou 1995;Schlegel et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The dates and coordinates of target fields are given in Table 2. The location of six target fields in the Carina dSph galaxy was purposely chosen to overlap the Wide Field Imager (WFI) field from Dall'Ora et al (2003), as shown in Figure 1. The HAWK-I field of view of four 2048 × 2048 pixel detectors was about 7 ′ .…”
Section: Observations Data Reduction and Calibrationmentioning
confidence: 99%
“…The list of variables from Dall'Ora et al (2003) served as a reference to cross-identify 33 RRL (29 RRab + 4 RRc) stars in our fields. Although our six HAWK-I fields overlapped the WFI field only 30% of the time (see Figure 1), the sample of identified RRL stars constitutes 61% of the sample of Dall'Ora.…”
Section: Identification Of Variablesmentioning
confidence: 99%
See 2 more Smart Citations